Activities of daily living in myotonic dystrophy type 1. (21st January 2020) - Landfeldt, Erik; Nikolenko, Nikoletta; Jimenez‐Moreno, Cecilia; Cumming, Sarah; Monckton, Darren G.; Faber, Catharina G.; Merkies, Ingemar S.J.; Gorman, Grainne; Turner, Chris; Lochmüller, Hanns
Abstract : Objectives: The objective of this cross‐sectional, observational study was to investigate performance of activities of daily living in patients with myotonic dystrophy type 1 (DM1). Materials and Methods: Adults with genetically confirmed DM1 were recruited from Newcastle University (Newcastle upon Tyne, UK) and University College London Hospitals NHS Foundation Trust (London, UK). Data on activities of daily living were recorded through the DM1‐Activ C (scale scores range between 0 and 100, where a higher/lower score indicates a higher/lower ability). Results: Our sample comprised 192 patients with DM1 (mean age: 46 years; 51% female). Patients reported most difficulties with running, carrying and putting down heavy objects, and standing on one leg, and least difficulties with eating soup, washing upper body, and taking a shower. Irrespective of the disease duration (mean: 20 years), most patients were able to perform basic and instrumental activities of daily living (eg personal hygiene and grooming, showering, eating, cleaning and shopping), with the exception of functional mobility/transfer tasks (eg walking uphill and running). The mean DM1‐Activ C total score was estimated at 71 (95% CI: 68‐74). Estimated progenitor cytosine‐thymine‐guanine repeat length and age explained 27% of the variance in DM1‐Activ C total scores ( P  < .001). Conclusions: We show that DM1 impairs performance of activities of daily living, in particular those requiring a high degree of muscle strength, stability and coordination. Yet, across the evolution of the disease, the majority of patients will still be able to independently perform most basic and instrumental activities of daily living.